1990
DOI: 10.1002/aja.1001890103
|View full text |Cite
|
Sign up to set email alerts
|

Three structures associated with the nucleolus in male rat germinal cells: Round body, coiled body, and “nubecula” and general presence of round body at male meiosis

Abstract: In addition to chromosomes and nucleoli, three structures, i.e., round body, coiled body, and nubecula, are encountered in the nucleus during the meiotic prophase in male rats. These structures have been examined by electron microscopy in random and serial sections. The round body is a finely fibrillar, proteinaceous structure closely associated with the granular component of a nucleolus in rat spermatocytes and young spermatids. A similar structure has been observed in man, the monkey Macaca mulatta, the gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Coiled bodies are typically described at the ultrastructural level as oval to spherical inclusions, ranging in size from 0.3-0.9 tim and giving the appearance of bundles of "knotted threads." They also appear to be highly conserved in evolutionary terms, showing a similar appearance in eukaryotes as diverged as plants and mammals (43,57) . While an extensive literature exists describing the appearance and occurrence of coiled bodies, few functional studies have been carried out to address their biological role.…”
Section: Discussionmentioning
confidence: 99%
“…Coiled bodies are typically described at the ultrastructural level as oval to spherical inclusions, ranging in size from 0.3-0.9 tim and giving the appearance of bundles of "knotted threads." They also appear to be highly conserved in evolutionary terms, showing a similar appearance in eukaryotes as diverged as plants and mammals (43,57) . While an extensive literature exists describing the appearance and occurrence of coiled bodies, few functional studies have been carried out to address their biological role.…”
Section: Discussionmentioning
confidence: 99%
“…This nuclear organelle was later reidentified by electron microscopy and renamed the "coiled body" because of its appearance as loosely packed coiled fibrils (Monneron and Bernhard, 1969). Subsequent studies detected coiled bodies in animal and plant nuclei, showing that it is a conserved structure (Moreno Diaz de la Espina et al, 1980;Seite et al, 1982;Schultz, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This nuclear organelle was later reidentified by electron microscopy and renamed the "coiled body" because of its appearance as loosely packed coiled fibrils (Monneron and Bernhard, 1969). Subsequent studies detected coiled bodies in animal and plant nuclei, showing that it is a conserved structure (Moreno Diaz de la Espina et al, 1980;Seite et al, 1982;Schultz, 1990).Coiled bodies have been shown to contain splicing small nuclear ribonucleoproteins (snRNPs) and small nuclear RNAs (snRNAs), a subset of nucleolar components -including fibrillarin, Nopp140, NAP57, and U3 small nucleolar ribonucleoprotein (U3 snoRNP) -and the protein p80 coilin, which has been widely used as a marker for coiled bodies (Lamond and Earnshaw, 1998;Matera, 1998). The function of coiled bodies is still under debate, but several hypotheses have been proposed that are not necessarily mutually exclusive.…”
mentioning
confidence: 99%
“…They are never associated with or included in the nucleoli. This excludes any similarity with the round bodies (Schultz 1990), the nubecula and the coiled bodies. The last mentioned also contain hnRNPs (Fakan et al 1984), which have not been found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They contain heterogeneous ribonucleic acids (hnRNAs), are associated with or are included in the nucleoli and have a diameter of 0.4±1.6 m. (3) The ªnubeculaº (Schultz 1990) have been described as having a diameter of 0.5 m and are compact and faintly stained structures surrounded by a pale halo. They are present in rat primary spermatocytes in stages I±VI of the seminiferous epithelium.…”
Section: Introductionmentioning
confidence: 99%